A Brief History Of Yayasan Pengajian Tinggi Islam Kelantan (YPTIK) Nilam Puri And The Perception Of Its Alumni - Idris Awang,; Mat Nafi , Linamalini; Muhammad Razaki , Marina; Abdullah, Ashikin Aini Abdullah (Jurnal KIAS, 2020)
YPTIK was established in 1965 with nine objectives of historical and contemporary relevance. The institution, established under the Kelantan State Government Enactment 9/1968, was widely recognized by the universities of the Middle Eastern countries and its graduates proved to fare well in their undergraduate and postgraduate studies in those universities. The programmes offered, adapted from the curriculum of Al-Azhar University, were of Islamic Studies disciplines especially in Shariah and Usuluddin with Arabic as the medium of instruction. Laws, Economics and Sociology were also taught to expose students to contemporary issues. YPTIK had contributed significantly to the Malaysian society with its graduates serving in educational, Islamic legal and judiciary as well as economic and political sectors. The perception of the alumni is significantly high in terms of their alma mater's impact on professional success -- they feel proud to be the alumni of YPTIK. their academic and professional success --they feel proud to be the alumni of YPTIK.